Exploring the sugar-sweetened beverage tax (SSBT) pass-through rate in the Irish hospitality sector - Frank Houghton; J. Moran Stritch; J. Auerbach; M. Daly; D. Houghton (BMC, 2024)
Abstract Background The World Health Organization (WHO) supports the use of Sugar-Sweetened Beverage Taxes (SSBTs) as a fiscal lever to help reduce sugar consumption and tackle obesity. Obesity is associated with a range of adverse health outcomes. In response to increasing levels of obesity in Ireland, an SSBT was introduced in 2018. Previous research in Ireland has noted that the pass-through rate of the SSBT in retail (off-site consumption) settings was poor. However, to date, no research has examined the SSBT pass-through rate in hospitality (on-site consumption) venues in Ireland. Methods This research examines the SSBT pass-through rate on Coca-Cola versus diet versions of Coca-Cola in a convenience sample of 100 hospitality venues in two provincial Irish cities. Results Wilcoxon signed rank test analysis revealed that regular Coca-Cola was significantly more expensive compared to the price charged for diet versions of Coca-Cola. However, in 85.6% of cases the same price was charged for both full-sugar and sugar-free drinks. The mean pass-through rate of the SSBT was 33.8%. Conclusion The effective functioning of the SSBT is premised on persistent price differences between soft drink prices based on sugar content. However, this is barely evident in the hospitality sector in Ireland. A number of recommendations are suggested, including both increasing the SSBT, and increasing it annually in line with inflation.